Translator and Translated Twice Removed: Multilingual Selfhood in Rabih Alameddine's An Unnecessary Woman. Issue 2 (August 2021) - Lvovich, Natasha
Abstract : This article analyses the novel An Unnecessary Woman (2013) by the American-Lebanese writer Rabih Alameddine from the perspective of multilingual selfhood, echoing Borges's vision of 'writing as translation' as it expands to considerations of literary translingualism. The narrator/protagonist of the novel, Aaliya Saleh, is a translator whose main occupation is translation into Arabic from the existing English and French translations: from literary West into East. The significance of the author's creative choice of what is referred to as a twice-removed translator is explored with the following questions: How, while navigating between two languages, cultures, and identities, is the multilingual individual experiencing the balancing act between the 'translation' and the 'original'? To what extent are characters, generated by writers' translingual imagination, indeed creative (re)incarnations of the author's fragmented self? Is there such a thing as the fidelity to an original' for an immigrant (the author)? What can we learn about this translingual polyphony of voices when it comes from the area of political conflict and deepening economic/humanitarian crisis?